A Choirbook for the Seven Sorrows: Royal Library of Belgium, Ms. 215-16: Study - Thelen, Emily; Bossuyt, Ignace (Leuven Alamire Foundation Antwerpen Davidsfonds Uitgeverij, 2018)
Brussels, Royal Library of Belgium Ms. 215-16 is a choirbook belonging to the Alamire corpus, a group of richly illuminated manuscripts preserving sixteenth-century sacred and secular music from the Low Countries. This manuscript is unique among the collection because all of its music celebrates a central theme: the Seven Sorrows of the Virgin.Devotion to the Virgin’s Sorrows was immensely popular in the early sixteenth century among all levels of society – from labourer to nobility. As an artifact of this widespread movement, this exceptional choirbook not only commemorates the devotion through both polyphony and plainchant but also reveals its importance for the Burgundian- Habsburg court.
Keywords: 16th Century (1501-1600); Music history; Choir; Book; Mass